PENGARUH SELF – LEADERSHIP, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR PDAM KABUPATEN GIANYAR - Dewa Ayu Diyah Maharani; Pande Ketut Ribek; Tiksnayana Vipraprastha (EMAS, 2024)
The aim of this study is that to explain the influence of self-leadership, work discipline, and motivation on employee performance at PDAM Office Gianyar Regency. Furthermore, the populations in this study were 189 employees and the methods for determining the sample size used in this study were the Yamane and Isaac and Michael formula in order to obtain 65 samples. Meanwhile, the data analysis technique used was multiple linear regression analysis by using the Statistical Program of Social Science (SPSS) version 25.0 for Windows. The results of this study show that; (1) self-leadership has a positive and significant influence on employee performance, (2) work discipline has a positive and significant influence on employee performance, and (3) motivation has a positive and significant influence on employee performance. It is expected for further research to develop this study by adding other variables.